Photocatalytic Degradation of Aqueous Rhodamine 6G Using Supported TiO2 Catalysts. A Model for the Removal of Organic Contaminants From Aqueous Samples - Pino, Eduardo; Calderón, Cristian; Herrera, Francisco; Cifuentes, Gerardo; Arteaga, Gisselle (Frontiers in Chemistry, 2020)
As a model for the removal of complex organic contaminants from industrial water effluents, the heterogeneous photocatalytic degradation of Rhodamin 6G was studied using TiO2-derived catalysts, incorporated in water as suspension as well as supported in raschig rings. UV and Visible light were tested for the photo-degradation process. TiO2 catalysts were synthesized following acid and basic methodologies and compared against commercial TiO2 catalyst samples (Degussa P25 and Anatase). The bandgap (Eg) of the TiO2 catalysts was determined, were values of 2.97 eV and 2.98 eV were obtained for the material obtained using acid and basic conditions respectively, and 3.02 eV for Degussa P25 and 3.18 eV for anatase commercial TiO2 samples. Raschig rings-supported TiO2 catalysts display a good photocatalytic performance when compared to equivalent amounts of TiO2 in aqueous suspension, even though a large surface area of TiO2 material is lost upon support. This is particularly evident by taking into account that the characteristics (XRD, RD, Eg) and observed photodegradative performance of the synthesized catalysts are in good agreement with the commercial TiO2 samples, and that the RH6G photodegradation differences observed with the light sources considered are minimal in the presence of TiO2 catalysts. The presence of additives induce changes in the kinetics and efficiency of the TiO2-catalyzed photodegradation of Rh6G, particularly when white light is used in the process, pointing towards a complex phenomenon, however the stability of the supported photocatalytic systems is acceptable in the presence of the studied additives.. In line with this, the magnitude of the chemical oxygen demand, indicates that, besides the different complex photophysical processes taking place, the endproducts of the considered fotocatalytic systems appears to be similar.